Resolving the Judiciary Tensions between the Constitutional Court and the Supreme Court of Indonesia - Purwadi, Hari; Hermawan, Sapto; Soares, Ardyllis Alves; Németh-Szebeni, Zsófia; Kusuma, Febrian Indar Surya (Universitas Negeri Semarang, 2024)
This paper addresses a critical issue undermining the legal coherence and judicial stability in Indonesia: the discord between the Constitutional Court and the Supreme Court in the realm of judicial review. This paper uncovers the root cause as a weak chain of validity in law formation, aggravated by divergent legal frameworks governing each court through utilizing doctrinal research methods. Drawing on Bullygin's deontic logic theory, the paper reveals a lack of explicit cross-sectoral policy synchronization. To immediately alleviate these tensions, this paper proposes the establishment of a Memorandum of Understanding (MOU) between the two courts, aiming to solidify the chain of legal norms and restore systemic stability. For a long-term resolution, a comprehensive revision of the judiciary law is advocated. This research serves as an urgent call for coordinated reforms to bolster the integrity and efficiency of Indonesia's judicial system.